The multifceted personality of Luis Antonio Calvo (2013)
The present work was originally a conference that the author read in one of the rooms of the Auditorium “Luis A. Calvo” of the Industrial University of Santander, during the celebration of one of the first Piano Festivals that have been held since 1984, in the Bucaramanga city. On that occasion the author was seconded in the musical examples with the help of a pianist. What follows is a revised, revised and expunged version of the original content. With the help of examples of romantic, post-Romantic and nationalist composers from Europe and America, especially the so-called salon pieces, the author manages to demonstrate the true influences and compositional abilities operating in the piano pieces of Luis A. Calvo and how he is quite wrong Call it the Colombian Chopin.